Enhancing students’ problem-solving skills and energy-saving character through a physics e-module - Widya, Widya; Andriani, Riza; Mujtahid, Zainul; Muttakin, Muttakin; Nurpatri, Yeni (Indonesian Journal of Science and Mathematics Education, 2026)
The low level of students’ problem-solving skills and awareness of energy-saving behavior highlights the urgency of developing contextual teaching materials aligned with the Merdeka Curriculum. This study aimed to develop and evaluate the effectiveness of a Creative Problem Solving (CPS)–based e-module to improve students’ problem-solving skills while fostering energy-saving character. The research employed a quasi-experimental design with a pretest–posttest control group. The sample comprised two eleventh-grade science classes purposively selected from a senior high school in Aceh Utara Regency, Indonesia. Effectiveness analysis was conducted by comparing learning outcomes between the experimental and control groups. The results indicate that the CPS-based e-module effectively improved students’ problem-solving skills, with an average N-Gain score of 71.73, classified as high. In addition, the e-module contributed positively to the development of energy-saving character, as reflected in improvements in most indicators (frugality, accuracy, tolerance, and creativity) toward habitual behavior. These findings imply that CPS-based e-modules have the potential to serve as integrated learning innovations that enhance instructional quality while fostering energy-saving character at the secondary education level.